2012
DOI: 10.1097/fbp.0b013e32835651c9
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of methamphetamine-induced and cocaine-induced one-trial behavioral sensitization in preweanling and adolescent rats

Abstract: The ontogenetic profile of psychostimulant-induced one-trial behavioral sensitization has not been determined. The purpose of this study was to systematically assess the ontogeny of methamphetamine- and cocaine-induced behavioral sensitization across the preweanling and adolescent periods. To this end, rats were injected with methamphetamine, cocaine, or saline in either an activity chamber or home cage during the preweanling (PD 12, PD 16, or PD 20), preadolescent (PD 24), or adolescent (PD 34) periods. One d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 64 publications
2
17
0
Order By: Relevance
“…In a series of studies, we previously reported that young rats show strong one-trial behavioral sensitization, but the age at which sensitized responding was exhibited depended on the psychostimulant being administered (McDougall et al 2011a, 2013; Kozanian et al 2012). For example, amphetamine and METH caused the most robust sensitized responding at PD 13 and PD 17, while cocaine only produced behavioral sensitization in older animals (i.e., at PD 21).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a series of studies, we previously reported that young rats show strong one-trial behavioral sensitization, but the age at which sensitized responding was exhibited depended on the psychostimulant being administered (McDougall et al 2011a, 2013; Kozanian et al 2012). For example, amphetamine and METH caused the most robust sensitized responding at PD 13 and PD 17, while cocaine only produced behavioral sensitization in older animals (i.e., at PD 21).…”
Section: Discussionmentioning
confidence: 99%
“…Ontogenetic studies examining the preweanling period have shown that cocaine-induced one-trial behavioral sensitization is strongest when assessed around PD 21, whereas METH- and amphetamine-induced one-trial sensitization is most robust at PD 17 (Kozanian et al 2012; McDougall et al 2013). Cocaine and METH sensitization was either weak or not evident at the opposing ages (Kozanian et al 2012).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with some, but not all, previous studies. A study (Kozanian, Gutierrez, Mohd‐Yusof, & McDougall, 2012) found, albeit using stimulants other than AMPH or MPH, a sensitized response to the repeated administration of methamphetamine or cocaine in preweanling, but not in adolescent, rats. Conversely, adolescent but not adult mice exhibited greater motor activity to a challenge dose of AMPH (2.0 mg/kg), after a history of exposure to 10.0 mg/kg AMPH (Adriani et al., 1998).…”
Section: Discussionmentioning
confidence: 99%